An investigation of the implementation of the Employment Equity Act (No. 55 of 1998) of South Africa by organisations in Cape Town in the Western Cape - Thabethe, Wandile (Department of Social Development, 2023)
The South African Government has committed itself to redressing the injustices of the past by passing laws such as the Employment Equity Act No. 55 of 1998. The Act was promulgated for the purpose of bringing equity and parity to the workplace. However, findings from this research study and other initiatives, such as those from the Employment Equity Commission Report of 2017, reveal that South African organisations are still predominantly run by White males. This study then sought to find out why the implementation of the Act has not resulted in more people of colour ascending into management positions. A qualitative research method was employed as a methodology for the study, while using structured face-to-face interviews as a data collection tool. The study's population was a convenience sample of human resource managers working for corporate organisations in Cape Town, in the Western Cape. To collect the data, 20 human resource managers were interviewed for close to an hour each. Once the data was collected, it was transcribed and then analysed using Creswell's data analysis spiral, which moves in analytic circles instead of a fixed linear approach. The findings of this study revealed that management in corporate Cape Town was still predominantly the preserve of White males. The organisations that participated in this study indicated that their management was comprised of individuals who were experts in their fields and who have been with these organisations for extended periods of time. As a result, it was not easy to move them out of such positions as the organisations would be losing out on their expertise; rather they waited for them to age and retire or voluntarily resign. Some organisations had succession plans for managerial positions, however, the problem they faced was that several individuals who were part of the succession plan were impatient and ended up leaving the organisations, taking up offers elsewhere. Other organisations without succession plans or with individuals who were not yet ready for management positions, struggled to find Black candidates to fill the positions. In one case, a qualified Black candidate refused an offer because he was to be relocated to Cape Town. In addition, disabled individuals do not seem to be considered part of the Employment Equity policies as organisations are more focused on Black people and women, and neglect disabled people. Overall, findings show that organisations in the Western Cape are committed to the Employment Equity Act, however it will take some time before Blacks, people with disabilities and women to fill management positions.